Neonatal epididymo-orchitis caused by Salmonella: A case of successful non-surgical management - Avaneesh Kunta; Samantha Gibson; Abhishek Seth; Kenneth A. Alexander; Adriana Cadilla; Pamela Ellsworth (Urology Case Reports)
Neonatal epididymo-orchitis (EO) is a rare condition, particularly when caused by Salmonella, a pathogen typically associated with gastroenteritis. We present the case of a 15-day-old male who developed right-sided scrotal swelling and erythema. Scrotal ultrasound confirmed EO without signs of torsion or abscess. Further investigation revealed potential Salmonella exposure from feeding bottles, and stool PCR confirmed the diagnosis. The patient responded well to antibiotics, avoiding surgical intervention. This case highlights the rarity of Salmonella EO in neonates and the value of early imaging, thorough history-taking, and environmental exposure assessment in guiding conservative management and avoiding surgery.